2015
DOI: 10.1039/c5an00838g
|View full text |Cite
|
Sign up to set email alerts
|

High resolution ion mobility-mass spectrometry for separation and identification of isomeric lipids

Abstract: Lipidomics is a particularly difficult analytical challenge due to the number and importance of isomeric species that are known or postulated in biological samples. Current separation and identification techniques are too often insufficiently powerful, slow or ambiguous. High resolution, low field ion mobility coupled to mass spectrometry is shown here to have sufficient performance to represent a new alternative for lipidomics. For the first time, drift-tube ion mobility separation of lipid isomers that diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
188
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(209 citation statements)
references
References 35 publications
(66 reference statements)
8
188
0
2
Order By: Relevance
“…2000 (Table 1), which is approximately an order of magnitude higher than current state-of-the-art instrumentation. 4850 It should be noted, however, that this determination of separation potential for closely related isomers in Table 1 ( i.e. , within 0.4%) is based solely on the observable percent difference in CCS, which, for these small differences is approaching the certainly limit of the measurement (± 0.2–0.3%).…”
Section: Resultsmentioning
confidence: 90%
“…2000 (Table 1), which is approximately an order of magnitude higher than current state-of-the-art instrumentation. 4850 It should be noted, however, that this determination of separation potential for closely related isomers in Table 1 ( i.e. , within 0.4%) is based solely on the observable percent difference in CCS, which, for these small differences is approaching the certainly limit of the measurement (± 0.2–0.3%).…”
Section: Resultsmentioning
confidence: 90%
“…Separating these compounds based purely on mobility alone would require 280 resolving power or less, which is currently obtainable (Table S2). 30,57,61 To separate ca. 95% (CCS ≥ 0.02%) of the peptides by IM alone would require about 7,000 mobility resolving power.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by Baker and coworkers (49) reported that positional isomers of phospholipids could be differentiated by IM separation, but the difference between the drift times of each pair of isomers is less than 1%, which is beyond the resolution of our instrument. In another study by Groessl et al (52), the effect of E/Z isomers on the CCS of PC(18:1/18:1) was also found to be less than 0.5%.…”
Section: Ccs Measurements Of Lipids By Twim-ms Calibrationmentioning
confidence: 99%